Work together anywhere : a handbook on working remotely successfully : for individuals, teams & managers - Sutherland, Lisette (John Wiley & Sons, Inc., 2020)
'An excellent guide on how teams can effectively work together, regardless of location.' 'STEPHANE KASRIEL, former CEO of Upwork IN TODAY'S MODERN GLOBAL ECONOMY, companies and organizations in all sectors are embracing the game-changing benefits of the remote work'place. Managers benefit by saving money and resources and by having access to talent outside their zip codes, while employees enjoy greater job opportunities, productivity, independence, and work-life satisfaction. But in this new digital arena, companies need a plan for supporting efficiency and fostering streamlined, engaging teamwork. In Work Together Anywhere, Lisette Sutherland, an international champion of virtual-team strategies, offers a complete blueprint for optimizing team success by supporting every member of every team, including: - Employees advocating for work-from-home options - Managers seeking to maximize productivity and profitability - Teams collaborating over complex projects and long-term goals - Organizations reliant on sharing confidential documents and data - Company owners striving to save money and attract the best brainpower Packed with hands-on materials and actionable advice for cultivating agility, camaraderie, and collaboration, Work Together Anywhere is a thorough and inspiring must-have guide for getting ahead in today's remote-working world.